PENGARUH UKURAN PERUSAHAAN, KEBIJAKAN DIVIDEN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN - Floretta Michelle; Sugiarto Prajitno (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to obtain empirical evidence of the return on asset, debt to equity ratio, current ratio, firm size, dividend payout ratio, current ratio, firm size, dividend payout ratio, managerial ownership, and institutional ownership on firm value as dependent. The population in this research is non-financial companies, that listed in Indonesia Stock Exchange (IDX) from the period 2018 to 2020. The sample used consists of 48 companies. This sample uses a purposive sampling method. The data analysis methods used multiple regression analysis. The results showed that profitability and leverage had an effect on firm value. Meanwhile, liquidity, firm size, dividend policy, managerial ownership, and institutional have no effect on firm value.